2017
DOI: 10.4172/2167-0420.1000392
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Unwanted Pregnancy and Associated Factors among Women in Reproductive Age Groups at Selected Health Facilities in Addis Ababa, Ethiopia

Abstract: Background: Unsafe abortions resulting from unintended pregnancies denote an important public health challenge throughout the world. Although various strategies have been used to address this problem unsafe abortion from unwanted pregnancy remained the cause for a significant number of maternal morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 5 publications
4
25
4
Order By: Relevance
“…Women of secondary and higher schooling were more likely to undergo an abortion [11,[15][16][17]. Other determinants of pregnancy termination include maternal media exposure, contraceptive use, women's autonomy, [10,18], marital status [19,20], birth order, parity [10] and religion [11]. Women who have been exposed to the media and who were contraceptive non-user more are likely to undergo an abortion.…”
Section: Introductionmentioning
confidence: 99%
“…Women of secondary and higher schooling were more likely to undergo an abortion [11,[15][16][17]. Other determinants of pregnancy termination include maternal media exposure, contraceptive use, women's autonomy, [10,18], marital status [19,20], birth order, parity [10] and religion [11]. Women who have been exposed to the media and who were contraceptive non-user more are likely to undergo an abortion.…”
Section: Introductionmentioning
confidence: 99%
“…In this study married respondents were more likely to have pregnancy compared to respondents who were not married. Unlike studies done in antenatal care unit shows being unmarried was potential exposing factor for unintended pregnancy (2,3,12,14,28,29,32,33). This might be due to respondents who were not married may not have sexual contact in turn they could not have unintended pregnancy.…”
Section: Discussionmentioning
confidence: 87%
“…It is shown that out of 210 Million pregnancies occurring globally, nearly 80 million of them were unintended each year [2]. Recently, unintended pregnancy in Africa was reported to be 57 per 1000 female university students [3,4]. In Sub-Saharan Africa 14 million unintended pregnancies occur every year, with almost half occurring among women aged 15-24 years [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations